Validation of Two Preoperative Kattan Nomograms Predicting Recurrence After Radical Prostatectomy for Localized Prostate Cancer in Turkey: A Multicenter Study of the Uro-oncology Society - (:unkn) unknown (ELSEVIER SCIENCE INC, 2009)
OBJECTIVES To examine, in a multicenter validation study designed under the guidance of the Uro-Oncology Society, the predictive accuracies of the 1998 and 2006 Kattan preoperative nomograms in Turkish patients. These 2 preoperative Kattan nomograms use preoperative parameters to estimate disease recurrence after radical prostatectomy. METHODS A total of 1261 men with clinically localized prostate cancer undergoing radical prostatectomy were included. The preoperative prostate-specific antigen level, biopsy Gleason score, clinical stage, number of positive and negative prostate biopsy cores, and postoperative recurrence status of all patients were studied. The predicted values using the Kattan nomograms and the observed values were compared. RESULTS The patient characteristics in the cohort were comparable with those of the cohorts used to create the Kattan nomograms. The 5-year probability of freedom from recurrence was 73% using Kaplan-Meier analysis and was similar to that of the 1998 Kattan nomogram cohort. However, the 10-year probability of freedom from recurrence was 67%, slightly lower than the same estimate from the 2006 nomogram cohort. The predicted values of recurrence using Kattan nomogram and the observed rates in our cohort were similar. The estimated concordance index value was 0.698 and 0.705 for 1998 and 2006 nomograms, respectively. CONCLUSIONS The Kattan preoperative nomograms can be used with adequate success in Turkey, because the predicted and observed rates in our cohort were similar. Our results have demonstrated satisfactory concordance index values, suggesting that both the 1998 and the 2006 Kattan preoperative nomograms can safely be used in Turkish patients with similar accuracy. Although the 2006 nomogram had slightly better discrimination, the 1998 nomogram was a little more calibrated. UROLOGY 74: 1289-1295, 2009. (C) 2009 Published by Elsevier Inc.
Keywords: PATHOLOGICAL STAGE; ANTIGEN; COHORT; MEN